Sex, desire, and taboo in South Asia: religion, culture of ability, and patriarchy - Acharya, Tulasi (Lexington Books, 2024)
"Sex, Desire, and Taboo in South Asia investigates how religion, ability culture, patriarchy, and taboos impact sex and desire in South Asia. Through analysis of theories of sexuality alongside erotic literature, the book underscores the need for intersectional approaches when discussing taboos around the world"--